1979
DOI: 10.1144/gsjgs.136.5.0569
|View full text |Cite
|
Sign up to set email alerts
|

A review of the main structural and magmatic features of northern Sumatra

Abstract: Structural and magmatic features of northern Sumatra are reviewed, based on a continuing programme of reconnaissance mapping. Distinction is drawn between Tertiary sedimentation on the W and that in the centre and E, the dividing line being the main outcrop of the Sumatran Fault System (SFS) which traverses the length of the island. Large transcurrent movements on the SFS are indicated by ( a ) regional slivers of oceanic crust trapped at the leading junction of the western continental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 5 publications
0
40
0
Order By: Relevance
“…2) that has been a topic of considerable interest for many years. Page et al (1979) and Fauzi et al (1996) suggested there may be a slab tear beneath Sumatra, possibly linked to the Investigator Fracture Zone, which may be related to the Toba volcanic centre (Chesner, 1998(Chesner, , 2012Chesner et al, 1991). Lange et al (2010) also suggested the Investigator Fracture Zone may influence seismicity and presumably slab morphology.…”
Section: Mantle Structure Of Se Asia: Larger Scale Patterns and Earlymentioning
confidence: 99%
See 1 more Smart Citation
“…2) that has been a topic of considerable interest for many years. Page et al (1979) and Fauzi et al (1996) suggested there may be a slab tear beneath Sumatra, possibly linked to the Investigator Fracture Zone, which may be related to the Toba volcanic centre (Chesner, 1998(Chesner, , 2012Chesner et al, 1991). Lange et al (2010) also suggested the Investigator Fracture Zone may influence seismicity and presumably slab morphology.…”
Section: Mantle Structure Of Se Asia: Larger Scale Patterns and Earlymentioning
confidence: 99%
“…Toba has been linked to subduction of the Investigator Fracture Zone on the Indian plate (e.g. Page et al, 1979), who suggested a tear at the fracture zone. Its cause could be a weakness due to the fracture zone which is being subducted subparallel to the postulated tear.…”
Section: Sumatramentioning
confidence: 99%
“…They observe that this mode of terrane emplacement may be more common than generally believed, particularly in orogenic belts developed in response to oblique convergence. Examples of this type of emplacement can be found in the Philippines (Karig et al, 1986), Halmahera (Hall, 1990), and Sumatra (Page et al, 1979). A similar scenario may be applicable to the Western Sulawesi ophiolite fragments.…”
Section: Discussionmentioning
confidence: 91%
“…Tangse valleys. This is essentially a right lateral fracture system [13]; [14]. The topographical morphology of the study area (Blang Bintang) is weak (soft) because the rocks are strongly fractured and altered.…”
Section: Geological Settingmentioning
confidence: 99%